The effect of E-commerce on the audit profession - Elaimin, Anas Abdelbagi (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to identify the most important challenges facing the audit profession in the light of the companies that deal with electronic commerce and to show the impact of electronic commerce on auditing standards and to clarify the impact of electronic commerce on audit procedures and rules. The researcher surveyed all the literature related to the subject of the study following the historical inductive approach. The study reached a number of results the most important of which were, there are major challenges facing the auditing profession after the large emergence of E-commerce companies. Based on the results the researcher suggested a number of recommendations most notably of which were, Synchronization between the publication of the accompanying financial statements of the companies through the website of the auditor and the company's website as long as that the company refers to its website to publish a copy of these financial statements on the website of the Capital Market Authority for companies listed on the capital market.
Keywords: impact; e-commerce; auditing profession; auditor